Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

A tropical lady beetle, Diomus lupusapudoves (Coleoptera: Coccinellidae), deceives potential enemies to predate an ant-protected coffee pest through putative chemical mimicry - Aaron Iverson; Robyn Burnham; Ivette Perfecto; Natalia Vandenberg; John Vandermeer (International Journal of Tropical Insect Science, 2022)

Species complementarity in two myrmecophilous lady beetle species in a coffee agroecosystem: implications for biological control - Aaron Iverson; Doug Jackson; Robyn Burnham; Ivette Perfecto; Natalia Vandenberg; John Vandermeer (BioControl, 2018)

Distribution, diversity, and traits of native, exotic, and invasive climbing plants in Michigan - Robyn J. Burnham; Cristine V. Santanna (Brittonia, 2015)

No evidence that elevated CO 2 gives tropical lianas an advantage over tropical trees - David C. Marvin; Klaus Winter; Robyn J. Burnham; Stefan A. Schnitzer (Global Change Biology, 2015)
Recent studies indicate that lianas are increasing in size and abundance relative to trees in neotropical forests. As a result, forest dynamics and carbon balance may be altered through liana‐induced suppression of tree growth and increases in tree mortality. Increasing atmospheric CO 2 is hypothesized to be responsible for the increase in neotropical lianas, yet no study has directly compared the relative response of tropical lianas and trees to elevated CO 2 . We explicitly tested whether tropical lianas had a larger response to elevated CO 2 than co‐occurring tropical trees and whether seasonal drought alters the response of either growth form. In two experiments conducted in central Panama, one spanning both wet and dry seasons and one restricted to the dry season, we grew liana ( n = 12) and tree ( n = 10) species in open‐top growth chambers maintained at ambient or twice‐ambient CO 2 levels. Seedlings of eight individuals (four lianas, four trees) were grown in the ground in each chamber for at least 3 months during each season. We found that both liana and tree seedlings had a significant and positive response to elevated CO 2 (in biomass, leaf area, leaf mass per area, and photosynthesis), but that the relative response to elevated CO 2 for all variables was not significantly greater for lianas than trees regardless of the season. The lack of differences in the relative response between growth forms does not support the hypothesis that elevated CO 2 is responsible for increasing liana size and abundance across the neotropics.

Diversity and abundance of climbers from the Atlantic Forest, southeastern Brazil - Berta Lúcia Pereira Villagra; Eduardo Pereira Cabral Gomes; Robyn J. Burnham; Sergio Romaniuc Neto (Biodiversity and Conservation, 2013)

Book review - Robyn J. Burnham (Plant Systematics and Evolution, 2004)

Book reviews - Robyn J. Burnham (Plant Systematics and Evolution, 2004)